ASUPAN ZAT GIZI, INFEKSI DAN SANITASI DENGAN STUNTING ANAK USIA TIGA TAHUN DI WILAYAH PEDESAAN - Sugeng Wiyono; Titus Priyo Harjatmo; Trina Astuti; Nanang Prayitno; Nils Aria Zulfianto; Tugiman A.S; Ratih Puspaningtyas P; Annas Burhani; Farha Fahira (Poltekkes Kemenkes Semarang, 2020)
Background: The impact of stunting children is an enhancement in the incidence of morbidity and mortality, development cognitive, motoric, nonoptimal children verbal, enhancement of health costs, nonoptimal as an adult, enhancement risk of obesity, decreased health of reproduction, low capacity of learning, productivity and also work capacity which is not optimal.Purpose: The objective of this research is to find out overview of nutritional intake, infection and sanitation against stunting children under aged tree years.Method: The research design was cross section with the population of a household that have a children aged 6-35 months. A sample of 368 children aged 6-35 months were taken in a cluster.Results: There was no dependence on stunting with the length of birth (p0.05), and there was no dependance on stunting with the weight of birth (p 0.05). There is no relation between maternal education level with stunting (p 0.05). There is no relation between maternal energy intake with stunting (p 0.05). There was a significant difference (p = 0.025) on stunting based on giving feed or ekslusif breastmilk.Conclusion: There is a significant relationship between the time of complementary feeding with exclusive breastfeeding and the incidence of stunting children under aged three years.Suggestion: Education is required for prospective mothers or mothers who have babies for giving breastmilk (ASI) until the baby is six months old or exclusively breastfed.